The Individual and the Community in Stoic Pragmatism - Skowroński, Krzysztof Piotr (Ruch Filozoficzny, 2023)
The present paper outlines John Lachs’s idea of stoic pragmatism and develops its important part that is the relation between the individual and the community. In his project, Lachs reduces the whole tradition of Stoic philosophy to its later, Roman version and tries to link it with the philosophical tradition of American pragmatism (especially William James, John Dewey, and George Santayana, who is close to pragmatism at some points) hoping that it is possible for these two to "enrich and complete each other" so that to provide "a better attitude to life than either of the two views alone." Stoic pragmatism pursues factual improvement in the quality of life for individuals living in given social circumstances, rather than a new theory about such improvement. Interestingly, stoic pragmatism overlaps at many points with the so-called modern stoicism, a movement that uses Stoic ethics in contemporary contexts.